2017
DOI: 10.1039/c7ra07080b
|View full text |Cite
|
Sign up to set email alerts
|

A dodecanethiol-functionalized Ag nanoparticle-modified ITO anode for efficient performance of organic light-emitting devices

Abstract: The electroluminescence intensity of a dodecanethiol-functionalized silver (DT-Ag) NP/ CPB:Ir(mpidmb) 2 (acac) film was increased by about 2.23 times in comparison with that of a control device, CPB:Ir(mpidmb) 2 (acac), due to coupling between excitons of emissive layer and the localized surface plasmon resonance (LSPR) of DT-Ag NPs. The current efficiency of a device with a DT-Ag NPs layer at 100 cd cm À2 (42.3 cd A À1) was 17.0 cd A À1 higher than that of the control device (25.3 cd A À1).The increase in cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…The β-methylene and the thiol proton resonate at 1.60 ppm (quintet, J = 7.58 Hz) and 1.39 ppm (unresolved multiplet) respectively, the methyl of the C12 carbon is found at 0.87 ppm (triplet, J = 6.90 Hz) and the remaining protons on C3–C11 form an unresolved multiplet at 1.26 ppm. 37 Fig. 3(b) shows an NMR spectrum of the reaction product formed upon reacting 1-dodecanethiol with Bi powder; two α-methylene groups from a disulphide moiety resonate as a triplet at 2.68 ppm ( J = 7.35 Hz); two β-methylene groups resonate at 1.67 ppm (quintet, J = 7.31 Hz) and between 1.26 and 1.39 ppm there is an unresolved multiplet formed by the protons on the two alkyl chains.…”
mentioning
confidence: 99%
“…The β-methylene and the thiol proton resonate at 1.60 ppm (quintet, J = 7.58 Hz) and 1.39 ppm (unresolved multiplet) respectively, the methyl of the C12 carbon is found at 0.87 ppm (triplet, J = 6.90 Hz) and the remaining protons on C3–C11 form an unresolved multiplet at 1.26 ppm. 37 Fig. 3(b) shows an NMR spectrum of the reaction product formed upon reacting 1-dodecanethiol with Bi powder; two α-methylene groups from a disulphide moiety resonate as a triplet at 2.68 ppm ( J = 7.35 Hz); two β-methylene groups resonate at 1.67 ppm (quintet, J = 7.31 Hz) and between 1.26 and 1.39 ppm there is an unresolved multiplet formed by the protons on the two alkyl chains.…”
mentioning
confidence: 99%
“…The Gaussian decomposition was resolved using the CasaXPS software (from Casa Software Ltd). As can be seen, the laser irradiation is able to break most of the (located at 368.1 eV and 374.1 eV, respectively) [38,39]. These results also present a small content of carbon which remains from the TGME solvent after the drying and sintering steps, as observed in inset of Figure 4c.…”
Section: Electrodes Characterizationmentioning
confidence: 65%
“…The ratio used between Cu and In in our research was also 1:1; however, it is noteworthy that our synthesis has differences when compared to the article by Zhang et al, which did not show diffractogram profiles at 2θ smaller 25°. Jayabharathi et al [ 31 ] developed copper/silver nanoclusters protected by DDT. The XRD profiles contained a series of peaks at low angles in the range of 2θ = 10–40°.…”
Section: Resultsmentioning
confidence: 99%
“…Jayabharathi et al [ 31 ] found two bands for the DDT associated with the asymmetric and symmetric stretching of methylene at 2920 and 2850 cm −1 , 2920 and 2850 cm −1 , respectively. GCIS/ZnS Qdots also have vibrations in these wavenumbers, with the asymmetric vibration at 2920 cm −1 , shifting to around 2917 cm −1 in the conjugated Qdots, which suggests an interaction between the DDT and the conjugated Qdots.…”
Section: Resultsmentioning
confidence: 99%